SILAKSAK Utilization as Support SAK-Based MSME Financial Digital Records - Sofian, Rudy; Ferdiansyah, Fahmi Reza; Hamidah, Hamidah; Nurrohmat, Muhamad Rizky; Dewi, Rahil Alya (Jurnal Akuntansi, 2024)
Purpose – Creating a SILAKSAK application for Saung Abah Ambu UMKM using the SAK EMKM standard. Design/methodology/approach – Software development using the Agile Feature Driven Development (FDD) method. A software development approach that prioritizes development based on the Develop an Overall Model, Build a Feature List, Plan by Features, Design by Feature and Build by Feature. In addition to using FDD, this software also uses a progressive web app (PWA) so that the SILAKSAK application can be installed on various platforms. Findings – The SILAKSAK application has run as expected, this is evident from the 17 functions tested, all 17 functions run well. In addition, partners feel helped by the recording using the SILAKSAK application because partners no longer need notebooks and partner finances can be accessed and monitored by partner owners. Research limitations/implications – Before implementing a financial application, partners must be equipped with knowledge about finance, for example what is a balance sheet, profit, ledger and others. Keywords: SILAKSAK, UMKM, FDD, Application